2013
DOI: 10.4028/www.scientific.net/amr.750-752.107
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, Dynamic Mechanical and Mechanical Properties of Long Glass Fiber Reinforced Polypropylene and Polyvinyl Chloride Composites

Abstract: The influence of long glass fiber (LGF) content on properties of PVC/PP composites were investigated by means of scanning electron microscopy (SEM), dynamic mechanical analysis (DMA), and mechanical properties. The experimental results demonstrate that long glass fiber could effectively improve the mechanical properties and storage modulus of PVC/PP. The DMA reveals good miscibility between PVC and PP. Based on SEM, good interfacial adhesion between matrix and long glass fiber in PVC/PP/LGF composites was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Based on these observations, it can be concluded that there is a relatively adhesion between PVC and the glass fibre used containing a carbon deposit on its surface [39,43]. The no visible reinforcement effect with simultaneously a good adhesion confirms the deterioration of the properties of the fibers used, also described in [16,19].…”
Section: Advances In Polymer Technologymentioning
confidence: 58%
See 1 more Smart Citation
“…Based on these observations, it can be concluded that there is a relatively adhesion between PVC and the glass fibre used containing a carbon deposit on its surface [39,43]. The no visible reinforcement effect with simultaneously a good adhesion confirms the deterioration of the properties of the fibers used, also described in [16,19].…”
Section: Advances In Polymer Technologymentioning
confidence: 58%
“…The reduction of impact strength and tensile strength of PVC composites with fibrous fillers is described in works [32,37]. However, in most cases, the addition of glass fibres in thermoplasts influences increase in the discussed mechanical properties [38][39][40][41][42]. The reduction of impact strength and tensile strength may be the result of insufficient adhesion between GFCD and PVC or deterioration of the mechanical characteristics of fibres in the pyrolysis process.…”
Section: Resultsmentioning
confidence: 99%
“…Glass fibre is predominantly used as the reinforcement material in LFT composites due to its low cost and superior mechanical properties. The most studied LFT is glass fibre-reinforced polypropylene (glass/PP) [14,20,22,[54][55][56][57][58][59][60][61][62][63], driven by its popularity in the automotive industry. Other fibres such as carbon fibre [27,29,35,39,64], basalt fibre [37,65,66], aramid fibre [67,68], PP fibre [69], polyimide fibre [33], and PET fibre [70] are also used as reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…Polyamide-based LFTs have about 20% of the market share and LFTs with other polymer systems comprise the remaining 15% [17]. Though single polymer systems are most commonly used as the matrix in LFTs, multiple polymer systems have also been studied such as TPU + POM [44], PP+ polystyrene (PS) [45], TPU + acrylonitrile butadiene styrene (ABS) [46], PBT + PET [47,48], polycarbonate + PBT [49], TPU + styrene acrylonitrile (SAN) [50], PA66 + PP [51,52], PP + PBT [53], and polyvinyl chloride (PVC)+PP [54]. LFTs with multi-matrix systems can gain the benefit of both the matrix polymers.…”
Section: Introductionmentioning
confidence: 99%